Effective properties of n-coated composite spheres assemblage in an ageing linear viscoelastic framework. (1st October 2017) - Honorio, Tulio; Bary, Benoit; Sanahuja, Julien; Benboudjema, Farid
Highlights: The GSC scheme is modelled in an ageing linear viscoelastic framework. The derivation is made using a formalism in terms of Volterra integral product. Estimations of relaxation and creep functions are provided. Comparisons with Mori-Tanaka estimations and FEM 3D simulations are provided. Abstract: The homogenization scheme based on n-coated spherical inclusion morphology, also called Generalized Self-Consistent (GSC) scheme, is derived in an ageing linear viscoelastic framework by using a formal treatment in terms of Volterra integral operator. Estimations of the bulk and shear relaxation functions as well as the creep functions are provided by numerical evaluation of the integral operator. The resulting (semi-)analytical estimations are compared to numerical simulations by Finite Elements Method (FEM) on 2-phase and 3-phase 3D numerical samples, and to Mori-Tanaka estimations in the 2-phase case.